All‐Solid‐State Batteries: Nano‐Scale Complexions Facilitate Li Dendrite‐Free Operation in LATP Solid‐State Electrolyte (Adv. Energy Mater. 26/2021). Issue 26 (15th July 2021) - Stegmaier, Sina; Schierholz, Roland; Povstugar, Ivan; Barthel, Juri; Rittmeyer, Simon P.; Yu, Shicheng; Wengert, Simon; Rostami, Samare; Kungl, Hans; Reuter, Karsten; Eichel, Rüdiger‐A.; Scheurer, Christoph
Abstract : In article number 2100707, Christoph Scheurer and co‐workers stabilize solid state electrolyte grains against Li dendrite nucleation and growth with a nanometer thin complexion. This naturally forming encapsulating layer serves as an effective electronic barrier while being permeable for Li ions. Future interfacial engineering could exploit a corresponding local separation of electronic and ionic flux at solid‐solid interfaces for rational advances in all‐solid‐state batteries.